Bioprotection on Chardonnay Grape: Limits and Impacts of Settling Parameters - Scott Simonin; Carole Honoré-Chedozeau; Ludovic Monnin; Vanessa David-Vaizant; Benoît Bach; Hervé Alexandre; Bertrand Chatelet; Raphaëlle Tourdot-Marechal (Australian Journal of Grape and Wine Research)
Background and Aims. If bioprotection has already been proven to limit the development of spoilage flora on musts, its effectiveness against oxidation depends on the winemaking process. To optimize its application, this study analyzed the evolution of the chemical composition of the bioprotected musts and wines, according to different settling routes. Their impacts on the organoleptic characteristics of wines were also studied. Methods and Results. A bioprotected must was subjected to 6 different maceration routes before AF (triplicates), varying the duration and temperature parameters. A temperature value ≤12°C was the main factor independently of the duration which allowed a good implantation of the bioprotectant. An increase of the maceration duration at 12°C led to browning of the must, without significant effect on the final color of the wine, which was felt as more “floral,” with more length in the mouth. Conclusions. The bioprotectant implantation and its effectiveness on the sensory profile of the wine was guaranteed at maceration temperature values lower than 12°C. Significance of the Study. This study participates in the improvement of the bioprotection management in white winemaking, with the guarantee of a positive impact of the prefermentation maceration without sulphites on the organoleptic profile of the wines.